The Micro-politics of Recognition and Care: How Adult Children in Urban China Negotiate Relationships with Emigrant Siblings. (12th June 2021) - Sun, Ken Chih-Yan; Kibria, Nazli
Abstract: This article offers the concept of "economies of recognition" to analyze the moral frames that siblings caring for left-behind parents in China use to negotiate intimate connections to their emigrant brothers and sisters. We argue that the impact of family dislocation on sibling relations is shaped by family members' co-constructed relational infrastructure. Our findings identify four types of relational infrastructure—collaboration, intrusion/interference, voluntary takeover, and feeling left behind—that mediate the impact of geographic proximity on parental caregiving. We suggest that the interplay between physical distance and elder care is emotionally experienced, interactionally evaluated, and symbolically understood. Understanding solidarity, conflicts, and ambivalence in the contexts of family crisis requires a close examination of how members of a care network attribute each other's roles and contributions to power symmetry or asymmetry. This explains why the advice, information, money, people, and emotions that are circulated are thought of as helpful resources in some cases but perceived as constraints in others.